Implementation of improved software defined radio modulation scheme and command and telemetry software interface for small satellites in 5G systems - Miranda, Ricardo Kehrle; da Costa, João Paulo C.L.; Roemer, Florian; Raschke, Florian; Eishima, Takashi; Nakamura, Yuya; Del Galdo, Giovanni (19th International Conference on OFDM and Frequency Domain Techniques, ICOF 2016, 2016)
Space systems are an ubiquitous part of modern society and the fast growth of the small satellite field is turning them applicable even for ubiquitous communications systems. Despite of their reduced size, the advances in miniaturization of electronic components are bringing a new level of capabilities and complexity to such machines. This work proposes an improved modulator using a software defined radio (SDR) architecture in the context of 5G systems since SDRs allow for the fast deployment of various transmission techniques such as Gaussian Minimum Shift Keying (GMSK), phase shift keying (PSK) and orthogonal frequency division multiplexing (OFDM). We validate our proposed modulator by applying low cost open source tools. Also, we propose a command and telemetry software design for advanced small satellites.
CRIS-Team Scopus Importer:2025-11-10